Clinical and design factors influence the survivorship of custom flange acetabular components. (June 2019) - Jones, C. W.; Choi, D. S.; Sun, P.; Chiu, Y-F.; Lipman, J. D.; Lyman, S.; Bostrom, M. P. G.; Sculco, P. K.
Abstract : Aims: Custom flange acetabular components (CFACs) are a patient-specific option for addressing large acetabular defects at revision total hip arthroplasty (THA), but patient and implant characteristics that affect survivorship remain unknown. This study aimed to identify patient and design factors related to survivorship. Patients and Methods: A retrospective review of 91 patients who underwent revision THA using 96 CFACs was undertaken, comparing features between radiologically failed and successful cases. Patient characteristics (demographic, clinical, and radiological) and implant features (design characteristics and intraoperative features) were collected. There were 74 women and 22 men; their mean age was 62 years (31 to 85). The mean follow-up was 24.9 months (sd 27.6; 0 to 116). Two sets of statistical analyses were performed: 1) univariate analyses (Pearson's chi-squared and independent-samples Student's t -tests) for each feature; and 2) bivariable logistic regressions using features identified from a random forest analysis. Results: Radiological failure and revision rates were 23% and 12.5%, respectively. Revisions were undertaken at a mean of 25.1 months (sd 26.4) postoperatively. Patients with radiological failure were younger at the time of the initial procedure, were less likely to have a diagnosis of primary osteoarthritis (OA), were more likely to have had ischial screws in previous surgery, had fewer ischial screw holes in their CFAC design, and had more proximal ischial fixation. Random forest analysis identified the age of the patient and the number of locking and non-locking screws used for inclusion in subsequent bivariable logistic regression, but only age (odds ratio 0.93 per year) was found to be significant. Conclusion: We identified both patient and design features predictive of CFAC survivorship. We found a higher rate of failure in younger patients, those whose primary diagnosis was not OA, and those with more proximal ischial fixation or fewer ischial fixation options. Cite this article: Bone Joint J 2019;101-B(6 Supple B):68–76.